Crystal Structure and Identification of Two Key Amino Acids Involved in AI-2 Production and Biofilm Formation in Streptococcus suis LuxS - Wang, Yang; Yi, Li; Wang, Shaohui; Fan, Hongjie; Ding, Chan; Mao, Xiang; Lu, Chengping (PLOS ONE, 2015)
Streptococcus suis has emerged as an important zoonotic pathogen that causes meningitis, arthritis, septicemia and even sudden death in pigs and humans. Quorum sensing is the signaling network for cell-to-cell communication that bacterial cells can use to monitor their own population density through production and exchange of signal molecules. S-Ribosylhomocysteinase (LuxS) is the key enzyme involved in the activated methyl cycle. Autoinducer 2 (AI-2) is the adduct of borate and a ribose derivative and is produced from S-adenosylhomocysteine (SAH). AI-2 can mediate interspecies communication and in some species facilitate the bacterial behavior regulation such as biofilm formation and virulence in both Gram-positive and Gram-negative bacteria. Here, we reported the overexpression, purification and crystallographic structure of LuxS from S. suis. Our results showed the catalytically active LuxS exists as a homodimer in solution. Inductively coupled plasma-mass spectrometry (ICP-MS) revealed the presence of Zn2+ in LuxS. Although the core structure shares the similar topology with LuxS proteins from other bacterial species, structural analyses and comparative amino acid sequence alignments identified two key amino acid differences in S. suis LuxS, Phe80 and His87, which are located near the substrate binding site. The results of site-directed mutagenesis and enzymology studies confirmed that these two residues affect the catalytic activity of the enzyme. These in vitro results were corroborated in vivo by expression of the LuxS variants in a S. suis ΔluxS strain. The single and two amino acid of LuxS variant decreased AI-2 production and biofilm formation significantly compared to that of the parent strain. Our findings highlight the importance of key LuxS residues that influence the AI-2 production and biofilm formation in S.suis.